EFEKTIVITAS PENGGUNAAN MEDIA BOARDGAME EDUKATIF DALAM PEMBELAJARAN SENI MUSIK UNTUK MENINGKATKAN PEMAHAMAN LAGU DAERAH SISWA KELAS VI SD NEGERI GUE GAJAH KABUPATEN ACEH BESAR - PIKRI; Aida Fitri; Mislinawati (Jurnal Pesona Dasar, 2026)
Students' low understanding of regional songs is a problem in Arts and Culture (SBdP) learning. This is due to the lack of interactive media that can improve students' understanding of regional songs. One effective medium for improving students' understanding of regional songs is Educational Board Game media. This study aims to examine the effectiveness of Educational Board Game media and the activities of teachers and students when implementing educational board game media. This research uses a qualitative approach with the Classroom Action Research (CAR) type. The subjects of this study were 16 Grade VI students and the homeroom teacher of SD Negeri Gue Gajah, Aceh Besar Regency as observer. Data collection techniques used observation sheets and tests. The data analysis technique in this study used percentage formulas for teacher and student activities, classical percentage formulas for tests, and a classical success indicator of ≥75%. The results of the data analysis showed an increase in teacher activity, from 75% to 96%, student activity to 68% to 81%, and student learning outcomes to 68% to 100%. Therefore, it can be concluded that educational board games can improve students' understanding of regional songs in grade VI of SD Negeri Gue Gajah, Aceh Besar Regency.